Swimming Performance of Rock Carp Procypris rabaudi and Prenant's Schizothoracin Schizothorax prenanti Acclimated to Total Dissolved Gas Supersaturated Water. (18th July 2017) - Wang, Yuanming; An, Ruidong; Li, Yong; Li, Kefeng
Abstract: Total dissolved gas (TDG) supersaturation is becoming an increasingly serious problem in the upper Yangtze River basin and has been identified as a potentially negative environmental effect of hydropower development and operations. Juvenile Rock Carp Procypris rabaudi and Prenant's Schizothoracin Schizothorax prenanti dwell in the upper reaches of the Yangtze River and were selected as experimental fish to evaluate the impact of TDG supersaturation on swimming performance. The results showed that the swimming speeds of Rock Carp and Prenant's Schizothoracin differed significantly under different exposure times to TDG‐supersaturated water (129–131%). Exposure of fish to supersaturated TDG for 2 and 4 h with no recovery resulted in significantly lower critical swimming (Ucrit ) and burst swimming (Uburst ) speeds compared with those of fish not exposed to supersaturated TDG. The Ucrit and Uburst values for Rock Carp not exposed to supersaturated TDG were 1.4–1.6 times higher than those of fish exposed to supersaturated TDG for 2 h and 1.9–2.0 times higher than those of fish exposed for 4 h. Similarly, the Ucrit and Uburst values for Prenant's Schizothoracin not exposed to supersaturated TDG were 1.4–1.8 times higher than those of fish exposed to supersaturated TDG for 2 h and 2.5–3.1 times higher than those of fish exposed for 4 h. Fish that were exposed to supersaturated TDG for 2 and 4 h and then allowed to recover for 2 d swam better than fish exposed to supersaturated TDG for the same amount of time without recovery. Although a 2‐d recovery improved swimming performance over that of fish not allowed to recover, only the Rock Carp (and not the Prenant's Schizothoracin) returned to the swimming speeds observed in the control fish not exposed to supersaturated TDG. The results of our research can be applied to the operation of hydropower stations and can contribute fundamental data for establishing water‐related environmental standards in China. Received December 4, 2016; accepted July 1, 2017 Published online October 11, 2017